Design, optimization, and evaluation of lyophilized lipid nanoparticles for mRNA-based pulmonary mucosal vaccination - Yicheng Lu; Yang Yang; Jing Yi; Xiaoxuan Hong; Jinghu Lou; Meng Li; Aiping Zheng (Materials Today Bio)
Lipid nanoparticles (LNP) have emerged at the forefront of the delivery of RNA molecules during the COVID-19 pandemic, leading to a giant leap in RNA therapies. Despite their great success, the long-term storage and transportation of mRNA vaccines without ultra-low temperatures is still challenging due to their poor stability. Here, we demonstrated that LNP-mRNA could be lyophilized via a simple freeze‒drying process. This process produced a dry powder formulation that could maintain the physicochemical properties of LNP-mRNA after storage at 4 °C for at least two months. However, the shear forces generated during the lyophilization process may disrupt the structure of the LNP, affecting the efficacy of the vaccine. Therefore, a cholesterol analogue, β-sitosterol, and a type of phospholipid, DOPE, were utilized instead of cholesterol and DSPC to improve the transfection efficiency after freeze-drying. The optimized formulation of LNP exhibited an enhanced transfection effect both in vitro and in vivo. Additionally, intratracheal administration of reconstituted lyophilized LNPs could induce innate cellular, humoral and mucosal immunity in vivo, indicating that our LNP-mRNA may serve as an effective vaccine against COVID-19. In summary, our study revealed that lyophilization of LNPs could increase their stability and maintain their ability to be transfected both in vitro and in vivo, inducing strong immune responses.